Cross-species comparison reveals therapeutic vulnerabilities halting glioblastoma progression - Förster, Leo; Kaya, Oguzhan; Wüst, Valentin; Danciu, Diana-Patricia; Akcay, Vuslat; Bekavac, Milica; Ziegler, Kevin Chris; Stinchcombe, Nina; Tang, Anna; Kleber, Susanne; Tang, Jocelyn L. Y.; Brunken, Jan; et al. (Nature Communications, 2025)
The growth of a tumor is tightly linked to the distribution of its cells along a continuum of activation states. Here, we systematically decode the activation state architecture (ASA) in a glioblastoma (GBM) patient cohort through comparison to adult murine neural stem cells. Modelling of these data forecasts how tumor cells organize to sustain growth and identifies the rate of activation as the main predictor of growth. Accordingly, patients with a higher quiescence fraction exhibit improved outcomes. Further, DNA methylation arrays enable ASA-related patient stratification. Comparison of healthy and malignant gene expression dynamics reveals dysregulation of the Wnt-antagonist SFRP1 at the quiescence to activation transition. SFRP1 overexpression renders GBM quiescent and increases the overall survival of tumor-bearing mice. Surprisingly, it does so through reprogramming the tumor’s stem-like methylome into an astrocyte-like one. Our findings offer a framework for patient stratification with prognostic value, biomarker identification, and therapeutic avenues to halt GBM progression.
Online veröffentlicht: 06. August 2025
Gesehen am TT.MM.JJJ